Nitpicking at the core of palaver - (:unkn) unknown (My University, 2019)
The palaver habit in Africa requires a place to exchange words and somme participants who are involved to negociate and promote a future social life are considered as nitpickers. Das one nitpick to better palaver, to reach the truth or to five a compromise?
Keywords: African Research